2010
DOI: 10.1002/pbc.22688
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis associated with precursor B acute lymphoblastic leukemia

Abstract: We report a case of a child with precursor-B acute lymphoblastic leukemia (ALL) who experienced refractory thrombocytopenia and massive splenomegaly during standard induction chemotherapy. He was diagnosed with hemophatocytic lymphohistiocytosis (HLH) during induction. Clinical and laboratory evaluation showed no evidence of infectious cause to HLH. Pancytopenia and HLH persisted after consolidation therapy even with remission from leukemia. After failure to control HLH with ALL-directed therapy and HLH-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This is a rare phenomenon, most commonly observed in the pediatric population. The association of HLH and ALL has been well described, [114][115][116][117][118][119][120][121][122][123] but unlike the case submitted to the workshop, in most reported cases, the diagnosis of ALL preceded HLH. In many cases, HLH has been associated with a concurrent infectious etiology, possibly due to immune deficiency following chemotherapy or stem cell transplantation for ALL, and in these patients, the term infection-associated hemophagocytic syndrome may be more appropriate.…”
Section: Is Therapy-related B-acute Lymphoblastic Leukemia/lymphoma Amentioning
confidence: 99%
“…This is a rare phenomenon, most commonly observed in the pediatric population. The association of HLH and ALL has been well described, [114][115][116][117][118][119][120][121][122][123] but unlike the case submitted to the workshop, in most reported cases, the diagnosis of ALL preceded HLH. In many cases, HLH has been associated with a concurrent infectious etiology, possibly due to immune deficiency following chemotherapy or stem cell transplantation for ALL, and in these patients, the term infection-associated hemophagocytic syndrome may be more appropriate.…”
Section: Is Therapy-related B-acute Lymphoblastic Leukemia/lymphoma Amentioning
confidence: 99%
“…28 Whereas MA-HLH has been reported with many different pediatric malignancies, in my experience, the most common associations are with anaplastic and nonanaplastic peripheral T-cell lymphomas often involving the skin and with leukemia, including acute monoblastic leukemia. We and others have described HLH occurring during induction therapy for B-precursor acute lymphoblastic leukemia (ALL), 29,30 and a review of the literature found 24 cases of HLH during and after therapy for B-and T-precursor ALL. 30 Several case reports of ALL presenting with HLH as the first manifestation of leukemia have been published, including a recent report of 2 patients with a heterozygous MUNC 13.4 mutation and a heterozygous perforin (PRF) gene mutation, respectively, who developed ALL within 1-4 months after therapy for HLH, 31 leading to speculation that abnormalities in these genes may increase the risk of malignancy.…”
Section: Ma-hlhmentioning
confidence: 99%
“…Similarly, Yoon et al reported that alloSCT could be a curative treatment not only for FHL, but also for relapsed/refractory sHLH (Yoon et al, 2010). Anecdotal reports have also shown the efficacy of alloSCT in M-HLH therapy (Chang et al, 2009;Goi et al, 1999;Kelly et al, 2011;Machaczka et al, 2011b).…”
Section: Stem Cell Transplantationmentioning
confidence: 99%